Evaluation of circularly polarized luminescence in a chiral lanthanide ensemble. Issue 1 (3rd October 2017) - Okayasu, Yoshinori; Yuasa, Junpei
Abstract : The circularly polarized luminescence of a chiral europium(iii ) (Eu III ) complex species has been successfully evaluated in an ensemble system. Abstract : This work demonstrates a methodology for the evaluation of circularly polarized luminescence of a chiral europium(iii ) (Eu III ) complex species in an ensemble system. The chiral Eu III complex species consists of chiral bis(oxazolinyl)pyridine [( R )- or ( S )-iPr-Pybox] and β-diketonate ligands with a pendant nitro group (DK-NO2 ). The pendant NO2 group in [iPr-Pybox](Eu III )(DK-NO2 )3 (monometallic Eu III species) coordinates to the Eu III center of another Eu III complex, giving rise to the generation of a chiral Eu III ensemble consisting of mono-, di-, and the other oligomeric Eu III species, [iPr-Pybox](Eu III )(DK-NO2 )3 n . The luminescence dissymmetry factors ( g lum ) of the chiral Eu III ensemble have been successfully determined by using a commercially available fluorescence spectrophotometer attached with a rotatable λ /4 filter and a fixed linearly polarized plate. This study suggests that the chiral Eu III ensemble in solution displays a large circularly polarized luminescence (| g lum | = 0.19) as compared to that of a reference monometallic complex [iPr-Pybox](Eu III )(DK-CN)3 (| g lum | = 0.11–13). The larger g lum is primarily attributed to the contribution of the dimetallic Eu III species exhibiting a high degree of circular polarization in luminescence ( g lum2 = 0.27) in the ensemble. Conversely, a large linearly polarized component was observed in luminescence from the chiral Eu III ensemble in the solid state (KBr pellet).